2020
DOI: 10.3390/en13195021
|View full text |Cite
|
Sign up to set email alerts
|

Multiobjective Optimisation of a Marine Dual Fuel Engine Equipped with Exhaust Gas Recirculation and Air Bypass Systems

Abstract: Dual fuel engines constitute a viable solution for enhancing the environmental sustainability of the shipping operations. Although these engines comply with the Tier III NOx emissions regulations when operating at the gas mode, additional measures are required to ensure such compliance at the diesel mode. Hence, this study aimed to optimise the settings of a marine four-stroke dual fuel (DF) engine equipped with exhaust gas recirculation (EGR) and air bypass (ABP) systems by employing simulation and optimisati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The genetic algorithm is a derivative-free optimisation method. Thanks to simplicity of implementation, it is very frequently used to solve numerous scientific and engineering tasks, such as: optimisation of gains of state observers [20], optimisation of controllers' parameters [21], optimisation of control policy in MPC [22], optimisation of settings for a fuel engine [23], optimisation of hybrid energy systems [24], integrated process planning, and scheduling [25].…”
Section: Genetic Algorithmmentioning
confidence: 99%
“…The genetic algorithm is a derivative-free optimisation method. Thanks to simplicity of implementation, it is very frequently used to solve numerous scientific and engineering tasks, such as: optimisation of gains of state observers [20], optimisation of controllers' parameters [21], optimisation of control policy in MPC [22], optimisation of settings for a fuel engine [23], optimisation of hybrid energy systems [24], integrated process planning, and scheduling [25].…”
Section: Genetic Algorithmmentioning
confidence: 99%
“…Finally, the engine torque, fuel consumption rate and emission parameters were optimized. Stoumpos et al [19] simulated and optimized the exhaust gas recirculation and air bypass system of a natural gas/diesel dual-fuel engine. The optimized dual-fuel engine was able to meet the International Maritime Organization's "Tier III" standard for NOx emissions in diesel-only operation.…”
Section: Introductionmentioning
confidence: 99%
“…Golzari et al studied the influence of water injection on the efficiency and emissions of a small single-cylinder gasoline direct injection engine, and the results showed that increasing water injection volume could improve the net efficiency of the engine while reducing emissions [19]. Stoumpos and Theotokatos used MOGA and design of experiment (DOE) parameters to optimize the engine and EGR/ABP (air bypass) system setting, and the results showed that the combination of EGR and ABP system enabled the engine emissions to meet more stringent regulatory requirements [20]. Cai et al optimized the EGR rate using the multiobjective gray situation decision method and Pareto frontier analysis method.…”
Section: Introductionmentioning
confidence: 99%